Peningkatan Kemampuan Disposisi Matematika Siswa Melalui Pembelajaran Model STAD - Indriyani, Mery; Izzati, Nurma; Muchyidin, Arif (JURNAL PENA EDUKASI, 2021)
AbstractThe purpose of this study is to determine the ability of students 'mathematical disposition through learning STAD models, to find out the increase in the ability of mathematical disposition through learning STAD models, and to assess whether increasing the ability of mathematical disposition of students through learning STAD models is better than increasing the ability of students' mathematical disposition through conventional learning and to find out students' responses to STAD learning models. This research uses a quantitative approach in the form of quasi experimental research. The experimental design used is the type of Nonequivalent control group design. The design is used to determine the ability of students' mathematical disposition before and after being given the STAD model. Increasing students' mathematical disposition abilities using STAD learning models obtained a percentage increase of 12%. The control class with a total of 31 student scores before treatment was 89.77 and after treatment was 97.26 with an average score difference of 7.49. Increasing the ability of mathematical disposition that uses conventional learning has a percentage increase of 8%. This shows that the mathematical disposition ability of the experimental class students is higher than the control class.Keywords: STAD, mathematical disposition, Nonequivalent control group design AbstrakTujuan dari penelitian ini adalah untuk mengetahui kemampuan disposisi matematika siswa melalui pembelajaran model STAD, untuk mengetahui besar peningkatan kemampuan disposisi matematika melalui pembelajaran model STAD, dan untuk mengkaji apakah peningkatan kemampuan disposisi matematika siswa melalui pembelajaran model STAD lebih baik dari pada peningkatan kemampuan disposisi matematika siswa melalui pembelajaran konvensional dan untuk mengetahui respon siswa terhadap pembelajaran model STAD. Penelitian ini menggunakan pendekatan kuantitatif yang berupa penelitian eksperimen kuasi. Desain eksperimen yang digunakan yaitu jenis Nonequivalent control group design. Desain tersebut digunakan untuk mengetahui kemampuan disposisi matematika siswa sebelum dan sesudah diberikan model STAD. Peningkatan kemampuan disposisi matematika siswa yang menggunakan pembelajaran model STAD didapat prosentase peningkatan sebesar 12%. Kelas kontrol dengan jumlah 31 siswa skor sebelum treatment adalah 89,77 dan sesudah treatment adalah 97,26 dengan selisih skor rata-rata sebesar 7,49. Peningkatan kemampuan disposisi matematika yang menggunakan pembelajaran konvensional memiliki prosentase peningkatan sebesar 8%. Hal tersebut menunjukkan bahwa kemampuan disposisi matematika siswa kelas eksperimen lebih tinggi dibandingkan kelas kontrol.Kata kunci: STAD, disposisi matematika, Nonequivalent control group design